Analysis of critical factors causing project close out delay at PT. Gas Mandiri - Wandi Siagian, Andre; Firman, Aries F (The Indonesian Journal of Business Administration, 2018)
Abstract: The Indonesian services sector has elevated in the last ten years. Urbanization growth and increasing consumer awareness about health and hygiene are factors expected to increase pest control service usage over the forecast period. This has driven to high demand for pest control services worlwide. Ahli Pest is one of the players in the industry is offering pest and termite control focusing on Jabodetabek market. The number of customer complaint and employee overtime rate is relatively high that indicates there are problems in operations division. The research is conducted through qualitative research by using interview to collect information from CEO and Operation Manager. The problems that occurs in the company will be analyzed by using Fishbone Diagram supported with root cause analysis in order to find the main problem. As result, there are three main problems that have to be solved immediately. They are high rate of employee overtime, high number of customers complaint, and high operating expenses. Those problems are related one to another. TQM is used to formulate proper operations strategy so it could be used to design policies by the company. In addition, Profit Plan Scenario is used so the company could set monthly sales target to fund operation expenses. Proper operations strategies are required in order to solve issues which are faced by the company in order to survive and grow in the competitive market. Ahli Pest needs to focus on creating policies, systems, and set sales target in order to survive and grow in the market. Keywords: Pest Control Services, Operations Strategy, Fishbone Diagram, TQM